Prevention of the Crime of Using Narcotics by Children as a Form of Opened System - Syarhan, Mohamad; Jaya, Nyoman Serikat Putra; Hartono, Bambang (International Journal of Criminology and Sociology, 2021)
This study aimed to find a model for the prevention of the use of narcotics by children as a form of the opened system. This needs to be done because seeing the number of users and dealers carried out by children. It is very concerned if children continuously carry out these actions. The research method used is a type of normative juridical research with a statute and conceptual approach. The technique of collecting data is through a library study by tracing secondary data. This study found that there are still many legal problems experienced by children, including criminal cases of narcotics use by children in Kuningan Regency and Padang City. This behavior requires prevention that does not harm the child’s future. This prevention can be implemented through the criminal justice system as an open system, where the settlement requires community involvement. Its implementation will consider the existing layers, including; society, political economy, education, technology, and the criminal justice system’s subsystems.